Building Knowledge Regions in North America: Emerging Technology Innovation Poles, Leonel Corona et al - Mercado Celis, Alejandro (Frontera Norte, 2017)
Cheltenham, Reino Unido, Edward Elgar Publishing, 2006, 304 pp